Izrekanje numinoznega pri utemeljiteljih simbolistične lirike - Mihelj, Sabina (Primerjalna književnost, 2000)
The voicing of numinous experience in the founders of symbolic lyricism. - The starting thesis of this article is that a specific language of poetry, as developed by symbolist poets, enabled poetry to become a privileged means of uttering modern religious (numinous, to be more precise) experience. An analysis of the interaction between the content and form of poems by four authors - Charles Baudelaire, Paul Verlaine, Arthur Rimbaud and Stéphane Mallarmé - shows that especially a (symbolist) use of a symbol, and the approach of poetry to music are important for the ability to express a numinous experience or object. In addition, the article deals with so-called sensual unreality (typical of Rimbaud's poetry) and pure poetry (typical of Mallarmé's poetry) and establishes how and why the symbolist poetry, which at first made an attempt to put into words numinous objects, was transformed intoa radical reflection on the nature of human realisation and utterance.
Keywords: Baudelaire, Charles, 1821-1867; Verlaine, Paul, 1844-1896; Rimbaud, Arthur, 1854-1891; Mallarmé, Stéphane, 1842-1898; francoska književnost; French literature; simbolizem; lirika; numinozno